The Relationship Between Time Management Skills and Academic Achievements of Nursing Students During the COVID-19 Pandemic - Emine Temizkan Sekizler; Kerem Yıldız; Nur Demet Gök; İncihan Kahraman; Bahar Ak Öskıran; Ufuk Kaya (Galenos Publishing House, 2022)
Objective:This study aims to determine the relationship between the time management skills of nursing students and their academic achievements during the COVID-19 pandemic.Method:The population of this descriptive study consisted of private University Health Sciences Faculty Nursing Department 2021-2022 Academic Year Fall Semester second year (n = 106), third year (n = 72), and fourth year (n = 88) students (n = 266). No sample selection was made in the study and the data were obtained from 182 students. The data of the study were collected online using the Participant Introduction Form and Time Management Questionnaire. Data analysis was performed using Statistical Package for Social Sciences 18.0 package software.Results:The mean score of the students on the time management inventory was found to be 90.93 ± 11.67. A statistically significant difference was found between the overall Time Management Questionnaire mean score and the variables of "presence of time-wasting factor during the distance education period" (p = .16) and "duration of social media use" (p = .13, p < .05). A statistical significance was found between the mean scores of the time attitudes subdimension and "presence of time-wasting factor during the distance education period" (p = .001) and "the duration of social media use" (p = .010, p < .05).Conclusion:The students' time management skills were determined to be at a "high" level, the factors that caused time loss during the distance education period and the duration of social media use affected the time management skills, and the time management skills did not affect academic success.